Examining the Difficulty of Discriminating Power and Distraction Quality of Daily Test Items about Basketball Material - Akromi, Hanif; Wiyanto, Agus; Astuti, Anjar Tri (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The purpose of this investigation was to evaluate the discriminatory power, difficulty level, and distractor quality of daily test items in class XI-F at SMA N 6 Semarang. Materials and Methods. The research method employed is a quantitative descriptive technique that is employed to assess the quality of test items. This is accomplished by analyzing test result data, answer keys, and student answer results. The resulting data is then processed using Anates V4 software to determine the level of difficulty, discriminating power, and distractor quality. Results. According to the study's findings, 86% of the test items exhibited favorable discrimination power, while 14% of the test items exhibited feeble or insufficient discrimination power. The difficulty level was 17%, while the moderate criteria were 46%. The simple category was as high as 37%. Very excellent distractors were rated at 11%, good distractors at 17%, less good distractors at 11%, and bad distractors at 15%. Distractors in the very bad category were rated at 46%. Conclusion. The discriminating power of the daily test questions on the subject of Physical Education and Health, basketball material for class XI-F of SMA Negeri 6 Semarang is primarily in the very good category. This implies that the quality of the queries effectively differentiates between students who have comprehended the material and those who have not. The majority are classified as moderate in terms of their level of difficulty. This implies that the queries have the potential to motivate students to exert more effort in resolving a specific issue. The quality of distractors is classified as very good (11%), good (17%), less good (11%), poor (15%), and very bad (46%).